Environmental Ethics in the Digital Economy: A Narrative Review of Corporate Responsibility and Sustainable Innovation - Yunus Indra Purnama; Junaidi Junaidi; Suparmono Suparmono (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2026)
The rapid growth of the digital economy has reshaped business models, production systems, and consumption patterns globally. Although digital technologies enhance efficiency and innovation, they also generate environmental challenges such as rising energy consumption, electronic waste, and the ecological impact of digital infrastructure. These issues have increased academic and policy focus on environmental ethics in contemporary business practices. This study aims to review and synthesize the literature on environmental ethics in the digital economy, with a focus on corporate responsibility and sustainable innovation. A narrative literature review method is applied, in which relevant peer-reviewed articles published between 2010 and 2024 were retrieved from Scopus using targeted keyword combinations, screened for relevance through title, abstract, and full-text review, and thematically synthesized to identify recurring conceptual patterns. The findings reveal four interrelated themes, synthesized in a thematic matrix. First, environmental ethics in business supplies the normative foundation for corporate environmental decision-making. Second, corporate environmental responsibility has become a key element of ethical governance in digital business contexts. Third, sustainable innovation and green technologies play a significant role in mitigating environmental impacts of digital transformation. Fourth, the integration of digital transformation and environmental sustainability shows that digital infrastructure itself generates environmental costs, such as rising energy consumption and e-waste, that require deliberate governance. Across these four themes, environmental ethics is increasingly embedded in corporate strategies, governance frameworks, and sustainability-driven business models, and an emerging fifth cluster on digital and artificial-intelligence ethics in ESG governance is identified as a direction for future research. This review strengthens the conceptual understanding of the relationship between environmental ethics, digital transformation, and sustainable innovation. The results underline the importance of aligning technological advancement with environmental responsibility. The study also provides implications for business leaders, policymakers, and researchers in promoting ethical and sustainable practices within the evolving digital economy.